Physical workload and risk of low back pain in adolescence. Issue 4 (22nd November 2011) - Mikkonen, Paula; Viikari-Juntura, Eira; Remes, Jouko; Pienimäki, Tuomo; Solovieva, Svetlana; Taimela, Simo; Zitting, Paavo; Koiranen, Markku; Leino-Arjas, Päivi; Karppinen, Jaro
Abstract : Objectives: To evaluate the role of physical workload in low back pain (LBP) among adolescents. Methods: Working history and physical workload factors at 18 years were assessed for 1984 members of the Northern Finland Birth Cohort 1986. The associations between work characteristics and LBP were analysed by multinomial logistic regression. Those with and without LBP at 18 years of age were compared in two subsamples. The incidence of LBP was studied among the 986 subjects without LBP at 16 years of age. Persistence of LBP was studied among the 728 subjects with LBP at 16 years of age. Latent class analysis (LCA) was used to form natural clusters of workload factors and their associations with LBP were investigated using log-binomial regression. Results: 753 (75%) subjects without LBP at 16 years of age had been working during the 2-year follow-up period. The average duration of work was 6.2 months. In adolescent girls, working regularly or irregularly and duration of work exposure were associated with incident LBP. Of specific physical workload factors, only awkward trunk postures were associated with incident LBP in both genders (RR 1.2 in girls and 1.7 in boys). The work exposure patterns in adolescent girls and boys were different. In the LCA, subjects in a cluster with high exposure to awkward trunk postures or an overall physically demanding job had a higher likelihood of incident LBP in both genders (RR 1.3–1.9). None of the specific workload factors or clusters was associated with persistent LBP. Conclusions: Physical workload factors constitute a risk for LBP even in adolescents.